Pola Konsumsi Tablet Ferros (FE) Pada Ibu Hamil Yang Mengalami Kekurangan Energi Kronik (KEK) Di Puskesmas Kurra Kabupaten Tana Toraja - Harmawati Rustan; Kartini S (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Chronic energy deficiency (CED) in pregnant women can also be interpreted as a situation when pregnant women have insufficient energy intake for a long period of time, causing the pregnant woman to gain less weight and can disrupt the health of the mother and fetus she is carrying. CED in pregnant women can trigger various health problems, such as anemia, respiratory tract infections, metabolic disorders, and increase the risk of complications during childbirth. The aim of this research was to determine the consumption pattern of Ferros (Fe) tablets among pregnant women who experience chronic energy deficiency (KEK) at the Kurra Health Center, Tana Toraja Regency. This research method is quantitative with a cross-sectional research design. The population in this study were 31 pregnant women who experienced Chronic Energy Deficiency (CED) at the Kurra Health Center, Tana Toraja Regency and the sample in this study were 31 pregnant women who experienced Chronic Energy Deficiency (KEK) at the Kurra Health Center, Tana Toraja Regency. pregnant mother. The sampling technique used in this research is total sampling where the researcher will take the entire population. This research was processed using a computerized system with the help of the SPSS program. The data analysis method used is statistical test analysis with a statistical test (chi-square) to determine the consumption pattern of Ferros (Fe) tablets in pregnant women who experience chronic energy deficiency (KEK), where if a p value of 0.000 < 0.05 is obtained, it can be interpreted as significant. Therefore, it is recognized that the pattern of consumption of Ferros (Fe) tablets in pregnant women who experience chronic energy deficiency (KEK)